Apicultural flora calendar for producers in the municipality of Major Izidoro, Alagoas - Cézar Augusto Tavares Alves; Maria do Carmo Carneiro (Universidade Estadual de Alagoas, 2021)
Resource availability and bee production in a particular locality are directly related to the floristic cover of the grazing area around the area where the hives are located. Therefore, the present work aimed to collect and identify the native and exotic apiculture flora, which produces apiculture resources around the area of two apiaries in the municipality of Major Izidoro, as well as to collect phenological data and preferential specimens visited by bees (Apis mellifera L.), which will ultimately be instrumental in measuring the final production of apiaries and enabling producers to schedule their apiaries from the production of a beekeeping calendar for the municipality. The present study was conducted in two distinct apiaries located in Major Izidoro municipality, Sertão Alagoano. With regard to their flowering phenophases (Table 1) most species remained flowering all year round and most months such as: Jatropha mollissima (Pohl) Baill. (Pinhão) which maintained its flowering from January to December, Cleome spinosa Jacq. (Munssambé) from January to August/November to December, Croton heliotropiifolius Kunth (Velame) from January to July/December, Cnidoscolus urens (L.) Arthur (Nettle) from January to March/May to December. In contrast, there were species that maintained their flowering for only one month during observation: Commelina erecta L (Santa Luzia Eye) and Indigofera suffruticosa Mill. (Indigo). The shortage of flowers occurred in the months of January, February and December, consequently the production of honey tends to decrease. However, because most plants have flowering most months, they can be indicated as important food sources for the local apifauna.